Autologous Bone Marrow Mononuclear Cells in Ischemic Cerebrovascular Accident Paves Way for Neurorestoration: A Case Report - Alok Sharma; Hemangi Sane; Anjana Nagrajan; Nandini Gokulchandran; Prerna Badhe; Amruta Paranjape; Hema Biju (Case Reports in Medicine)
In response to acute ischemic stroke, large numbers of bone marrow stem cells mobilize spontaneously in peripheral blood that home onto the site of ischemia activating the penumbra. But with chronicity, the numbers of mobilized cells decrease, reducing the degree and rate of recovery. Cellular therapy has been explored as a new avenue to restore the repair process in the chronic stage. A 67-year-old Indian male with a chronic right middle cerebral artery ischemic stroke had residual left hemiparesis despite standard management. Recovery was slow and partial resulting in dependence to carry out activities of daily living. Our aim was to enhance the speed of recovery process by providing an increased number of stem cells to the site of injury. We administered autologous bone marrow mononuclear cells intrathecally alongwith rehabilitation and regular follow up. The striking fact was that the hand functions, which are the most challenging deficits, showed significant recovery. Functional Independence Measure scores and quality of life improved. This could be attributed to the neural tissue restoration. We hypothesize that cell therapy may be safe, novel and appealing treatment for chronic ischemic stroke. Further controlled trials are indicated to advance the concept of Neurorestoration.